Enhancing mechanical properties of closed-cell lattice structure using various design variables - Chan, Jing Ling (Nanyang Technological University, 2023)
The toughness of closed-cell lattice structure was analysed through a set of variables, including the design of structure, lattice volume fraction, Young’s modulus, total elongation as well as ultimate tensile strength. The models were constructed in Abaqus to perform the simulations. The designs were in cubic foam, octet foam and combined cubic and octet foam, which were known to store maximum amount of strain energy. The highest toughness exhibited by plate octet truss with octet foam in a lattice fraction of 0.53 was explained. Furthermore, the effects of each variable on toughness were compared. Among the material properties, ultimate tensile strength was suggested to be the most effective factor to improve the toughness of closed-cell lattice structure, followed by total elongation and Young’s modulus. It was observed that the highest toughness could fall on composite and pure materials. As such, this study aimed to investigate the critical point where the toughness of composite can surpass the pure materials. It was done by plotting the toughness against the ratio of UTS between hard and soft materials. The upper and lower critical ratio were obtained and verified against testing groups.